Chemical Sensors Based on Two-Dimensional (2D) Materials for Selective Detection of Ions and Molecules in Liquid - Lee, Chung Won; Suh, Jun Min; Jang, Ho Won (Frontiers in Chemistry, 2019)
Up until now, two-dimensional (2D) materials have been researched vigorously for application to sensing ions and molecules in liquid due to their unique structural, chemical and electronic properties. Features of 2D materials such as high surface area-to-volume ratios and various reaction sites are ideal characteristics for fabricating state-of-the-art high-performed chemical sensors. This review particularly focuses on the detection of pH, metal ions and biomolecules in liquid media. The final goal of the ion/molecule sensors is a development of the electronic tongue or taste sensors that can be used in medical, food, biotechnology and health applications. Herein, we introduce recent advances in the field of ion/molecule sensors in liquid media based on 2D materials, especially concentrating in graphene and MoS2, and will emphasize the opportunities and challenges of these unique sensing materials and devices.